The impacts of animal welfare in quality of meat products of the sunite sheep (Mongolian Journal of Agricultural Sciences, 2019)
This study conducted the impacts of quality and safety on meat products of the Sunite sheep such as meat productions quality and yields, meat's physical and chemical characteristics, fat acids and amino acids, in conditions of animal welfare supplied and defferent nutritional status [9]. The main purpose of the research is to identify future measures to ensure that the human developments and foods health in the China, was there respect by humanitarian and ethical behavior and the basic conditions of animal welfare and to protect them from risks and dangers [7]. The Inner Mongolia should be promoting sustainable livestock farming, especially in developing ways to improve the efficiency of pastoral livestock, and ensuring the welfare of livestock to improve the quality and safety of livestock products. The methodology section summarizes the international methodology on how to assess animal welfare [2; 3]. The main results of this experiment are: 1) the growth of liveweight of the Sunite sheep increased as the age group was better, especially in the grazing group, 2) In connection studied between sheep feeding with the animal welfare and Sunite sheep meat productins value of n-3PUFA and n-6PUFA was higher than that depends of the sheep's age, 3) According to the slaughtering results, the yield of pure meat in animal welfare group was relatively higher than that of the insufficient group (P